Key Factors of Effectiveness of Developing an Activity Based Cost Accounting and Analysis System at an Enterprise - Y. V. Trifonov; A. N. Vizgunov (Учёт. Анализ. Аудит)
The article researches the problems related to the improvement of the efficiency of developing a system of activity based cost accounting and analysis at an enterprise based on a number of important factors. The first factor involves the organization of the accurate accounting of the most significant costs. The ABC model on the basis of the key costs will simplify the development of the system of cost accounting and make it possible to quickly modify its configuration in line with changes in economic and production environment conditions. The next factor implies the strict separation between the methods of analysis and modeling applied within the framework of a process management system and a system of activity based cost accounting and analysis. It helps to eliminate the errors connected with using wrong data as an information base for accounting. The third factor is using the data generated by information systems of an enterprise to calculate costs. The authors identify the information necessary to organize the activity based costing and determine within which kind of the information systems (ERP-system, EAM-system, etc.) it is formed. The use of this information will allow the enterprise to automate the cost calculation procedure and eliminate the additional work of data collection. The results of the analysis of these factors are the recommendations formulated by the authors to improve the efficiency of creation of activity based cost accounting and analysis system at an enterprise.